Spiritual Education Methods of the Naqshbandiyyah Order - Lubis, Zulfahmi; Zulham, Zulham (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study examines the methods of spiritual education implemented at the Suluk Langgar of the Naqshbandiyyah Order in Terjun Village, Medan Marelan, as a form of community-based non-formal Islamic education. This study employed a qualitative approach using a case study design. The primary data sources consisted of the mursyid, administrators of the langgar, and members of the suluk congregation who were directly involved in the spiritual education activities, while secondary data were obtained from institutional documents, activity records, and relevant written materials related to the implementation of the suluk practices. Data were collected through observation, in-depth interviews with the mursyid, administrators, and members of the suluk congregation, as well as documentation. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings show that spiritual education is conducted through religious study sessions (pengajian), tawajjuh and collective dhikr, the practice of suluk (spiritual retreat), and spiritual consultation. The applied methods include habituation of worship practices, gradual dhikr training such as dhikr ism al-dhāt, dhikr laṭā’if, dhikr nafy ithbāt, and dhikr wuqūf, along with spiritual discipline (riyāḍah rūḥāniyyah) and murāqabah under the close guidance of the mursyid. These methods are implemented systematically and progressively according to the spiritual readiness of the congregation. The study indicates that this model of spiritual education fosters inner tranquility, strengthens self-control, enhances courteous social behavior, and increases moral awareness in daily life. It concludes that the suluk practices of the Naqshbandiyyah Order at the Suluk Langgar in Terjun Village represent an effective and relevant model of non-formal Islamic education for spiritual and moral development in contemporary society.